2020
DOI: 10.20408/jti.2020.0047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resuscitative Endovascular Balloon Occlusion of the Aorta in Neurotrauma: Three Cases

Abstract: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is widely performed as an adjunct to resuscitation or bridge to definitive control of non-compressible torso hemorrhage in patients with hemorrhagic shock. It is a crucial adjunct for the maintenance of cerebral and coronary perfusion during resuscitation. However, in polytrauma patients with concomitant neurotrauma, such as traumatic brain injury (TBI) or spinal cord injury, the physiological effects of REBOA are unclear. In this report on REBO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…In our opinion REBOA placement is a safe procedure in a shocked patient where the treatment goals are to obtain a SBP improvement and a bleeding reduction, thus preserving cerebral perfusion pressure and reducing the impact of secondary brain damage [13] .…”
Section: Discussionmentioning
confidence: 98%
“…In our opinion REBOA placement is a safe procedure in a shocked patient where the treatment goals are to obtain a SBP improvement and a bleeding reduction, thus preserving cerebral perfusion pressure and reducing the impact of secondary brain damage [13] .…”
Section: Discussionmentioning
confidence: 98%
“…Resuscitative endovascular balloon occlusion of the aorta (REBOA) is commonly used as an adjunct to resuscitation and bridge to definitive control of non-compressible torso hemorrhage in patients with hemorrhagic shock 4 , 5 . It has also been performed for patients with neurogenic shock to support the central aortic pressure necessary for cerebral, coronary, and spinal cord perfusion 6 . Gray et al reported a case of successful REBOA in a patient with neurogenic shock secondary to a comminuted fracture at C5 with cord contusion.…”
Section: Refractory Neurogenic Shockmentioning
confidence: 99%
“…El REBOA se utiliza habitualmente como complemento de la reanimación y como puente para el control definitivo de la hemorragia no compresible del torso en pacientes con shock hemorrágico 6 , 7 . También se ha implementado en pacientes con choque neurogénico para mantener la presión aórtica central necesaria para la perfusión cerebral, coronaria y de la médula espinal 8 .…”
Section: Choque Neurogénico Refractariounclassified